Bats of Bako National Park, Sarawak, Malaysian Borneo - Faisal Ali, Anwarali; Siti Nurlydia, Sazali; Jayaraj Vijaya, Kumaran; Siali, Aban; Mohd Kasyfullah, Zaini; Besar, Ketol; Jeffrine Rovie, Ryan; Ahmad Mashur, Julaihi; L.S., Hall; Mohd Tajuddin, Abdullah (2007)
Two separate assessments on bats diversity were conducted in Bako National Park for about 12 trapping-nights. Our first assessment was conducted from 8th to 12th February 2005 followed by the second assessment on the 28th August to 3rd September 2005. A total of 295 individuals from 22 species of bats were captured using mist-nets and harp traps during the survey, which accumulated to 226 trapping-nights. Hipposideros cervinus was recorded as the most abundance species with 30.85% of total captures. Total of eight new geographic records have been added to this park: Emballonura monticola, Rhinolophus luctus, Hipposideros ater, Hipposideros bicolor, Myotis muricola, Myotis ater, Pipistrellus vondermanni and Kerivoula pellucida. With this additional record, now there are at least 34 species of bats known to occur in Bako National Park. A complete and long term study covering other areas not included in this study would definitely increase bat diversity found in these park.